Backwards computing. - Padavic-Callaghan, Kaimela (New Scientist, 2024)
The article discusses the concept of reversible computing as a potential solution to the energy demands of artificial intelligence and traditional computers. Reversible computing involves processors performing operations twice, once forwards and then in reverse, to reduce energy waste. The article highlights the environmental impact of AI, the inefficiency of standard computers, and the challenges in transitioning to reversible computing. Various companies are exploring different solutions to address the energy consumption of computing, with Vaire Computing leading the way in developing reversible computer chips.